Driver gene alterations in lung adenocarcinoma: Demographic features of 2544 Chinese cases. Issue 4 (December 2020) - Hu, Mingming; Zhang, Tongmei; Yang, Yuan; Che, Nanying; Li, Jie; Liu, Zichen; Li, Baolan
Background: To understand the association between driver gene variations and age and gender in patients with lung adenocarcinoma, we investigated mutations of the three most important driver genes—epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK) fusion genes and c-ros oncogene 1 (ROS1)—in this retrospective cohort study. Methods: Patients newly diagnosed with lung adenocarcinoma who received EGFR and ALK/ROS1 gene tests at our hospital from September 2014 to May 2019 were enrolled. EGFR mutations and ROS1 fusions were examined by ARMS-PCR and ALK fusions by Ventana-D5F3 IHC assay and ARMS-PCR. Results: Of 2544 eligible subjects, 2539 accomplished EGFR mutation tests. The prevalence of EGFR mutations was 62.1% in females, higher than that of 45.1% in males. In females, the EGFR mutation rate remained relatively stable at 60%–65% across the six age groups. Females showed an increased distribution of EGFR L858R and a decreased distribution of exon 19 deletion (19Del) by age. The incidence of ALK/ROS-1 rearrangements decreased significantly with age. Conclusions: EGFR 19Del mutation is more prevalent in younger males and females, while L858R mutation is prevalent in older females. Both ALK and ROS1 rearrangements are more common in younger lung adenocarcinoma. The young lung adenocarcinoma population is a distinct group rich in targetable genomic alterations, and more research is needed to understand the mechanism.